A Multimodal Explainable-AI Approach for Deep-Learning-based Epileptic Seizure Detection - Ashwini Patil; Megharani Patil (Journal of Electronics, Electromedical Engineering, and Medical Informatics, 2026)
Epilepsy carries a high risk of sudden death and increased premature mortality, highlighting the importance of automatic seizure detection to support faster diagnosis and treatment. The opacity of existing deep learning models limits their real-world application in diagnosing epileptic seizures, underscoring the need for more transparent and explainable systems. Limited research studies are available on Explainable Artificial Intelligence (XAI)-based epileptic seizure detection, and these studies provide only a visual explanation for the model’s behaviour. Additionally, these studies lack validation of the XAI outputs using quantitative measures. Thus, this research aims to develop an explainable epileptic seizure detection model to address the limitations of existing black-box deep learning approaches. It proposes a novel Hybrid Transformer-DenseNet121-XAI (HTD-MXAI) integrated model for detecting epileptic seizures from EEG data. The proposed model leverages advanced deep learning architectures, namely the Transformer and DenseNet121, for automatic feature extraction, while simultaneously extracting handcrafted features from the time, frequency, and spatial domains. The XAI techniques, such as Attention Weights, Saliency Maps, and SHapley Additive eXplanations (SHAP), are integrated with the proposed model to provide multimodal explainability for the model’s decision-making process. The results demonstrate that the proposed model outperforms state-of-the-art models for seizure detection. It achieves an overall (aggregated across subjects) accuracy of 99.14%, Sensitivity of 98.49%, and Specificity of 99.68% when applied to the CHB-MIT dataset. The Faithfulness score of 40.94% and completeness score of 1.00 indicate that the explanations provided by the XAI method for the model’s prediction are highly reliable. In conclusion, the proposed model offers a promising solution to the constraints, including the interpretability of black box models, limited multimodal explainability, and the validation of XAI techniques in the context of epileptic seizure detection.